Interdisciplinary management: periodontally accelerated osteogenic orthodontics in a patient with gingival recession. Case report - Huertas Campos, Mariana Cecilia (2019)
Periodontally accelerated osteogenic orthodontics is a procedure indicated to reduce the time of orthodontic treatment by giving an alternative treatment to periodontally compromised patients, with presence of root resorption, reduced periodontium, among others. Undiagnosed periodontal problems can be aggravated during orthodontic treatment and, depending on their severity, may require prior treatment. The objective of this report is to present the case of a patient with Class I malocclusion with crowding and gingival recession, treated with free tissue connective graft, corticotomy with bone graft and CCO Straighwire prescription technique. Finally, it can be concluded that interdisciplinary management is important for the correct diagnosis and treatment of patients. Periodontally accelerated osteogenic orthodontics is a viable alternative that reduces the time of orthodontic treatment and maintains or improves the periodontal condition of patients.